2021
DOI: 10.3390/s22010215
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography for Measuring Elevated Body Temperature: Clinical Accuracy, Calibration, and Evaluation

Abstract: Infrared thermographs (IRTs) implemented according to standardized best practices have shown strong potential for detecting elevated body temperatures (EBT), which may be useful in clinical settings and during infectious disease epidemics. However, optimal IRT calibration methods have not been established and the clinical performance of these devices relative to the more common non-contact infrared thermometers (NCITs) remains unclear. In addition to confirming the findings of our preliminary analysis of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 49 publications
0
33
0
1
Order By: Relevance
“…It has been proved that inner canthi (palpebral commissures) are considered to be optimal locations for non-contact temperature measurement. Perfused by the internal carotid artery, they are typically the warmest regions on the face and have high stability and strong correlation with internal body temperature [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that inner canthi (palpebral commissures) are considered to be optimal locations for non-contact temperature measurement. Perfused by the internal carotid artery, they are typically the warmest regions on the face and have high stability and strong correlation with internal body temperature [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors claim that it is possible and others correlate ROI surface temperatures with core body temperature [ 32 , 39 , 65 ], this research team chose to analyze the temperature of each ROI separately, without correlating them with core body temperature, since the team intends to embed this method to other algorithms developed, as well as further procedures under development in a single device. This proposal eliminates a data processing stage, decreasing the combined uncertainty of the final result, as well as the computational effort.…”
Section: Methodsmentioning
confidence: 99%
“…This may have a few potential causes. First, the FLIR Vue Pro camera is designed for drone image retrieval (https://www.flir.com/products/vue-pro/) and may not be a good choice for short-distance medical imaging, whereas two of the three IRTs used in this study have been evaluated for medical use [14], [16], [47]. Also, the thermal images we collected store raw temperature information.…”
Section: E Impact Of Image Background Intensity On Landmark Localizat...mentioning
confidence: 99%
“…IRTs detect infrared energy emitted from an object's surface and convert it to a temperature distribution image. Recent studies have demonstrated that IRT can effectively detect subjects with an elevated BT [14], [16]. While remote estimation of RR can be achieved through visible-light videos [17], there have been some efforts in this area using IRTs [10], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation